Environmentally relevant level of aflatoxin B1 elicits toxic pro-inflammatory response in murine CNS-derived cells. (5th September 2017) - Mehrzad, Jalil; Malvandi, Amir Mohammad; Alipour, Mohsen; Hosseinkhani, Saman
Graphical abstract: In vitro toxic pro-inflammatory effects of environmentally relevant level of aflatoxin B1 on CNS-derived cells could potentially translate to in vivo mammalian brain immune dysregulation and neurodegenerative disorders. Highlights: The effect of aflatoxin (AF) B1 on the function of murine CNS-derived cells with its LC50 was assessed. Post AFB1 -exposed microglia and astrocytes exhibit over expression of pro-inflammatory genes and proteins. AFB1 -exposed astrocytes' pro-inflammatory microenvironment results mainly from TLR mediated IL-6 load. Pro-inflammatory genes/proteins in AFB1 -exposed neural progenitor cells (NPC) were unchanged. Our novel finding confirms AFB1 is a potent neurotoxin in a mammalian in vitro model. Abstract: Aflatoxin B1 (AFB1 ) is a well-known member of aflatoxins (AFs) that is considered among highly stable toxic contaminants of food, worldwide. The impact of AFB1 on neural cells and systems has poorly been understood. To assess the cellular effects of AFB1 on brain, we used murine pure primary astrocytes, sub ventricular zone-derived neural precursor cells (NPCs) and microglia cell line (BV2). Cells were exposed separately to environmentally relevant level (20 ng/ml) of AFB1 for 1, 2, 3, 6, 12, 24 and 48 h in culture. At each time points, total free radicals production measured by luminol-enhanced cellular chemiluminescence (CL) assay; cytokines production of IL-1β, IL-6, TNF-α and IL-10 were analyzed using Bioplex ELISA and a set of genes involved in the immediate response to danger such as TLR2, TLR4 and iNOS etc . were evaluated by multiplex qPCR. Upon AFB1 exposure production, of the total free radicals significantly increased only in microglial cells after 24 h and slightly elevated in the other examined cells. AFB1 also induced secretion of pro-inflammatory cytokines ( i.e. TNF-α and IL-6) on both microglial cells (more TNF-α) and astrocytes (more IL-6). mRNA expression of TLR2, TLR4, MyD88 and NF-κB were up-regulated with different timing and levels among cells. Immunotoxicologically, microglial cells, and astrocytes, but not NPCs, are capable of sensing a low level of AFB1 . Thus, the pro-inflammatory effects of an environmentally relevant dose of AFB1 on CNS-derived cells in vitro could potentially explain the immune dysregulation in neurodegenerative disorders.